2015
DOI: 10.1515/helmin-2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Importance of complex diagnostic approach in differential diagnosis of alveolar echinococcosis

Abstract: SummaryAlveolar and cystic echinococcosis, serious parasitic diseases caused by larval stages of Echinococcus multilocularis and E. granulosus has been diagnosed in Slovakia for a long time. Study presents case of 49-years old patient with accidentally diagnosed one big (60 mm) and multiple small (2 -24 mm) hypoechogenic structures localised in right liver lobe. According to positive serology to E. granulosus antigen and results of imaging examinations the patient was classifi ed as possible case of cystic ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Our study revealed a 40 % (16/40) prevalence of Echinococcus multilocularis -the most dangerous zoonotic parasite for manwith a mean infection intensity of 1000 individuals (Table 1). Alveolar echinococcosis is a rare human disease that is often lethal if left untreated (Szilágyiová et al, 2015). It is caused by Echinococcus multilocularis at the larval stage.…”
Section: Resultsmentioning
confidence: 99%
“…Our study revealed a 40 % (16/40) prevalence of Echinococcus multilocularis -the most dangerous zoonotic parasite for manwith a mean infection intensity of 1000 individuals (Table 1). Alveolar echinococcosis is a rare human disease that is often lethal if left untreated (Szilágyiová et al, 2015). It is caused by Echinococcus multilocularis at the larval stage.…”
Section: Resultsmentioning
confidence: 99%
“…Alveolar echinococcosis is one of the most dangerous zoonoses in the world. While there are cases of human infection in some European countries (Horváth et al, 2008;Szilágyiová et al, 2015), there are no documented cases of human alveolar echinococcosis in Serbia at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only 18.4% prevalence of the tapeworm was recorded in the Košice region located in the eastern part of the country [ 29 ]. Human cystic echinococcosis occurs in Slovakia sporadically; two or three confirmed cases are reported every year [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar and cystic echinococcosis, serious parasitic diseases caused by the larval stages of Echinococcus multilocularis and E. granulosus sensu lato (s. l), have been diagnosed in Slovakia for a long time. The infection arises after the accidental ingestion of infective eggs from the contaminated environment (soil, water, food) and causes serious health problems connected primarily with effects on the liver [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%